2014
DOI: 10.3109/0886022x.2014.899874
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life, depression and mortality in peritoneal dialysis patients in Turkey: seven-year experience of a center

Abstract: Introduction: Impairment of health-related quality of life (HRQoL) and being in a depressive mood were found to be associated with increased mortality in peritoneal dialysis (PD) patients. We aimed to investigate the association between HRQoL, depression, other factors and mortality in PD patients. Materials and methods: Totally 171 PD patients were included and followed for 7 years in this prospective study. Results: Of 171 PD patients, 45 (26.3%) deceased, 18 (10.5%) maintained on PD, 87 (50.9%) shifted to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Another study investigated the association between the two variables in ESRD patients but did not perform subgroup analysis according to dialysis modality [31]. Other studies evaluated the association between the two variables in PD patients but used only SF-36 items [32,33]. The present study investigated KDQOL–SF including kidney disease–specific items and performed subgroup analyses of each dialysis modality.…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated the association between the two variables in ESRD patients but did not perform subgroup analysis according to dialysis modality [31]. Other studies evaluated the association between the two variables in PD patients but used only SF-36 items [32,33]. The present study investigated KDQOL–SF including kidney disease–specific items and performed subgroup analyses of each dialysis modality.…”
Section: Discussionmentioning
confidence: 99%
“…In the non-dialysis elderly general population, depression and frailty are additive risk factors for mortality and other adverse health outcomes [18][19][20]. In previous studies on dialysis patients, physical frailty [6,7] and depression [12,13] have each been shown to be associated with adverse clinical outcomes. Our results show that their effects in PD patients are also additive.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment is present in over 20% of dialysis patients [9,10], and is associated with increased risks of mortality and adverse clinical outcome [9,11]. Similarly, depressive symptoms are present in over 50% of PD patients [10] and is associated with excessive morality and represents a risk factor of peritonitis [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The score of each domain can range from 0 to 100, where higher scores indicate better HRQL or better health. The Turkish version of SF-36 has been used in different studies about hemodialysis patients and has been reported as valid and reliable (Kalender & Tosun, 2013;Turkmen et al, 2014). In this study, each domain's Cronbach's α ranges from 0.66 to 0.96.…”
Section: Short Form 36 (Sf-36)mentioning
confidence: 99%